Michael Vey : fall of Hades - Evans, Richard Paul (Evans, Richard Paul. Michael Vey series, 2016)
"Michael and the Electroclan embark on their deadliest mission yet. The head of the resistance, known only as the voice, believes that the best way to wipe out the Elgen is to steal their money. That means capturing the Joule, the Elgen boat that serves as a floating treasury. Michael and his friends have learned about a highly placed member of the Elite Global Guard named Welch who wants to defect. They also know that three of the Elgen electric youth have been condemned to death. If the Electroclan can rescue them and get to Welch first, they just might be able to steal the Joule. But it's a big if..."--